Overconsumption in Ethic Economics and Sustainable Development - Bidabad, Bijan (International Journal of Islamic Business & Management, 2019)
Squandering or spending more than need, which is a concept in ethic economics, which has been reconsidered under the subject of sustainable development at the present time. It is shown on the whole that the increase of per-capita consumption, the effects on the environment will increase; in other words, the environmental carrying capacity will decrease. At present world conditions, squandering means aggression to others’ rights and in addition to be disagreeable, but by compiling rules, it can be regarded in the domain of offense and crime at national and global levels. This is because squanderer endangers the environment and interests of others for her own benefit.As a model to use resources to serve human being needs for present and coming generations, sustainable development is put forward, which coincides with disagreeability of squandering in ethic economics. In spite of considering the sustainability of the environment, this concept takes into account the areas such as economics, socio-politics, and variety of cultural and life realms regarding intellectualism, sentiments, ethical and spiritual subjects. Regarding the chain of production, it also points to squandering as a topic in industrial ecology. Industrial ecology recommends converting industrial production processes from linear to circular systems in which, scraps and wastes are recycled as factors of other productions. Clean technology and its related regulations and cleaner production are also related to squandering concept in production. DOI: https://doi.org/10.5281/zenodo.3402347